Editor’s Foreword - Radaev, Vadim (Journal of Economic Sociology, 2022)
Dear colleagues, After the pleasant Christmas vacation, we are back to our routines. Universities have returned to conventional teaching of their classes, although nobody knows whether we will be able to keep these activities offline, given that a new strain of coronavirus, Omicron, is spreading around the world.